Sleep disturbances in nurses enrolled in part-time studies - Tomaszek, Tomaszek; Cepuch, Grażyna; Fugie, Beata (Nursing in the 21st Century, 2015)
SLEEP DISTURBANCES IN NURSES ENROLLED IN PART-TIME STUDIES Aim. The aim of this study was to assess the prevalence of sleep disorders among nurses enrolled in part-time studies and to identify the key factors affecting the sleep quality. Material and methods. The study was conducted on part-time student-nurses majoring in nursing. Sleep disorders were described using the Athens Insomnia Scale and the FIRST scale, as well as the author’s questionnaire. Data were analysed using Mann-Whitney U tests, ANOVA, Kruskal-Wallis and appropriate post-hoc tests. A significance criterion of P<0.05 was used throughout the study. Results. Sleep disorders were found in most student nurses – almost a half of them were at-risk of insomnia due to inadequate sleep hygiene. The main factors affecting sleep included nurses’ anxiety about their academic performance, stress, workload and shift work. Lack of sleep affected work performance the following day, leading to fatigue, increased daytime sleepiness, deterioration of concentration and irritability. Conclusion. Some individuals may not be aware about the relationship between one’s lifestyle and sleep quality which contributes to poor sleep quality and deteriorates one’s functioning during the day. In turn, this may lead to lower nursing care quality and it may also put additional strain on home chores.